Neural reward processing in individuals remitted from major depression. Issue 16 (28th August 2015) - Ubl, B.; Kuehner, C.; Kirsch, P.; Ruttorf, M.; Flor, H.; Diener, C.
Abstract : Background: Dysfunctional behavioural and neural processing of reward has been found in currently depressed individuals. However, little is known about altered reward processing in remitted depressed individuals. Method: A total of 23 medication-free individuals with remitted major depressive disorder (rMDD) and 23 matched healthy controls (HCs) performed a reward task during functional magnetic resonance imaging. We also investigated reward dependence, novelty seeking and harm avoidance using the Tridimensional Personality Questionnaire and their association with neural responses of reward processing. Results: Compared to HCs, individuals with rMDD exhibited enhanced responses to reward-predicting cues in the hippocampus, amygdala and superior frontal gyrus. When reward was delivered, rMDD subjects did not significantly differ from HCs. In both groups neural activity during reward anticipation was negatively correlated with harm avoidance. Conclusions: Our results show that rMDD is characterized by hyperactivation in fronto-limbic regions during reward anticipation. Alterations in neural activation during reward processing might reflect an increased effort in remitted depressed individuals to allocate neural activity for executive and evaluative processes during anticipatory reward processing.